CONSUMER ATTITUDES ON BUYING FISH IN BANJA LUKA - Ostojić, Aleksandar; Savić, Nebojša; Vaško, Željko (Economics of Agriculture, 2017)
The objective of research presented in the paper is to determine the basic parameters affecting he purchase, supply and consumption of fish in the market of the city of Banja Luka (Bosnia and Herzegovina). The survey was conducted on a random sample of 100 respondents. The data were analyzed by univariate (frequency and distribution) and two-variant statistical methods and cross-tabulation. The conclusions are that for the purchase of fish, freshness is a primary factor, which is to be expected given the type of product as well as the origin, and price and type of fish. Out of all respondents, 41% said they were not informed enough about the fish as a food, while the remaining 59% said they got information through different media channels. It was found that consumers are generally informed about the importance of fish as a foodstuff through secondary promotion channels, i.e. "word of mouth". Consumers in Banja Luka prefer fresh fish, and the most consumed is freshwater fish. As a place of buying fish, both hypermarket and fish shops are equally represented. Factors of purchase may have a major role in creating consumer attitude towards fish and therefore, producers and sellers of fish are recommended too take into account the results of this and similar studies, in order to segment their markets and develop better marketing tools/strategies and thus make better approach of fish consumers to defend market segments.